Cloning, expression, purification, and characterization of the murine lysosomal acid α-mannosidase - Merkle, Roberta K; Zhang, Yong; Ruest, Paul J; Lal, Anita; Liao, Yung-Feng; Moremen, Kelley W (Biochimica et biophysica acta, 1997)
Catabolism of α-linked mannose residues on eukaryotic glycoproteins is accomplished by a broad specificity lysosomal α-mannosidase (EC 3.2.1.24). Based on regions of protein sequence conservation between the lysosomal α-mannosidase from Dictyostelium discoideum and the murine Golgi glycoprotein processing α1,3/1,6-mannosidase, α-mannosidase II, we have cloned a cDNA encoding the murine lysosomal α-mannosidase. The longest of the clones was 3.1 kb in length and encoded a polypeptide of 992 amino acids containing a putative NH 2-terminal signal sequence and 11 potential N-glycosylation sites. The deduced amino acid sequence was 76.5% identical to the human lysosomal α-mannosidase and 38.1% identical to the lysosomal α-mannosidase from D. discoideum. Expression of the cDNA in Pichia pastoris resulted in the secretion of an α-mannosidase activity into the culture medium. This recombinant expression product was purified and was shown to have enzymatic characteristics highly similar to the enzyme purified from mammalian sources and to the human lysosomal α-mannosidase cDNA expressed in Pichia. These characteristics include a similar pH optimum, K m, V max, inhibition by swainsonine, and activity toward natural substrates. Northern blots identified a major 3.5 kb RNA transcript in all murine tissues tested. A minor transcript of 5.4 kb was also detected in some murine tissues similar to the alternatively spliced transcripts that have been previously identified in human tissues.